2018
DOI: 10.1097/igc.0000000000001143
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Versus Radiation Treatment for High-Grade Neuroendocrine Cancer of Uterine Cervix: A Surveillance Epidemiology and End Results Database Analysis

Abstract: Patients with cervical HGNECs had poor prognosis. Primary treatment by radical surgery or external beam radiotherapy with or without brachytherapy yielded equally poor survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Zhou et al 5 who analyzed data of 208 patients with stage I-II SCNEC found that age was an independent prognostic factor for OS (HR = 1.017, P = .004). Similarly, Hou et al 14 found a significant OS benefit in younger cases (P = .005) with high-grade neuroendocrine carcinoma in a retrospective analysis.…”
Section: Survivalmentioning
confidence: 73%
See 2 more Smart Citations
“…Zhou et al 5 who analyzed data of 208 patients with stage I-II SCNEC found that age was an independent prognostic factor for OS (HR = 1.017, P = .004). Similarly, Hou et al 14 found a significant OS benefit in younger cases (P = .005) with high-grade neuroendocrine carcinoma in a retrospective analysis.…”
Section: Survivalmentioning
confidence: 73%
“…Several reports have also found a worse survival outcomes with increasing age. 5,7,14 In a retrospective study of 130 patients with SCNEC, age older than 60 years was proved to be an independent prognostic factors for CSS regardless of stage. 7 Among the patients with IIB-IVB stage, those aged younger than 45 years had significantly lower risk of cancer death than those aged 45 to 60 years (HR, 3.4; P = .035).…”
Section: Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…Imaging and histological findings that have recently been added in the FIGO staging system are lymph node metastases. Other factors of importance include, e.g., minimum thickness of uninvolved cervical stroma, lymphovascular space invasion (LVSI), age, comorbidities (e.g., anemia, HIV infection), and high-risk histological subtypes, e.g., adenosquamous and neuroendocrine carcinomas [2932].…”
Section: Prognosis and Treatment In Relation To Figo Stagementioning
confidence: 99%
“…Our data showed that surgery and radiotherapy were associated with improved survival, but they failed to be prognostic predictors in multivariate analysis. Another prior SEER database analysis revealed that radical surgery and primary radiation yielded equally poor survival (5year OS rates were: 25% vs. 32%, p = 0.636) [26]. In China, radical hysterectomy-based surgery followed by adjuvant therapy is the primary treatment for patients with NECC in early FIGO stages [27].…”
Section: Discussionmentioning
confidence: 99%